Gait Impairment in Myoclonus–Dystonia (DYT-SGCE). (2nd August 2019) - Haeri, Ghazal; Shahidi, Gholamali; Fasano, Alfonso; Rohani, Mohammad
Background: Myoclonus–dystonia usually presents variable combination of myoclonus and dystonia mainly affecting the neck and arms, but leg involvement, especially as the presenting sign, is not common. Case report: A 29-year-old lady with a heterozygous mutation in Epsilon-sarcoglycan ( SGCE ) gene is presented with rapid jerks of the right leg interfering with walking. She has also manifested dystonic posture and jerks of the trunk and proximal upper limbs. Discussion: Although it is not typical, leg involvement could be a manifestation of myoclonus–dystonia either at presentation or during disease progression.